2014
DOI: 10.1186/bf03352163
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet application to the magnetic field turbulence in the upstream region of the Martian bow shock

Abstract: Wavelet analysis of the magnetic field fluctuations in the Martian foreshock is performed. Dynamical features of wave spectra are compared with plasma measurements of backstreaming ions and simulation results for all available data from the Phobos-2 spacecraft. A detailed analysis reveals the complex, fine structure of the ULF waves. It is shown that enhancement of this electromagnetic activity (mostly, at frequencies higher than the proton gyrofrequency) coincides with entry of the spacecraft into a bunch of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Skalsky et al (1992Skalsky et al ( , 1993 have demonstrated that the high frequency emissions at the leading edge of the foreshock are correlated with the enhanced electron fluxes streaming into the solar hemisphere along the magnetic field line. Tarasov et al (1998) presented the evidence that the ULF fluctuations of the magnetic field were observed simultaneously with the appearance of ions reflected at the Martian bow shock and gyrating in the upstream region (Dubinin et al, 1994(Dubinin et al, , 1995. All these phenomena have allowed to postulate the presence of a well developed foreshock upstream the Martian bow shock which is formally similar to that known from wave and plasma observations at Earth (Tsurutani and Rodriguez, 1981 and references therein).…”
Section: Introductionsupporting
confidence: 49%
See 1 more Smart Citation
“…Skalsky et al (1992Skalsky et al ( , 1993 have demonstrated that the high frequency emissions at the leading edge of the foreshock are correlated with the enhanced electron fluxes streaming into the solar hemisphere along the magnetic field line. Tarasov et al (1998) presented the evidence that the ULF fluctuations of the magnetic field were observed simultaneously with the appearance of ions reflected at the Martian bow shock and gyrating in the upstream region (Dubinin et al, 1994(Dubinin et al, , 1995. All these phenomena have allowed to postulate the presence of a well developed foreshock upstream the Martian bow shock which is formally similar to that known from wave and plasma observations at Earth (Tsurutani and Rodriguez, 1981 and references therein).…”
Section: Introductionsupporting
confidence: 49%
“…The ULF emissions measured in the frequency range between 0.2 and 10 Hz gradually increase in their amplitudes through out the entire foreshock region and their maximum intensities are recorded close to the shock front. Tarasov et al (1998) have shown that the local enhancements of the ULF magnetic oscillations were observed around the proton cyclotron frequency inside the Wave modes, which are typical for the electron and ion foreshock are indicated.…”
Section: Wave Observations In the Foreshock Region At Marsmentioning
confidence: 97%
“… Torrence and Compo [1998] provide a clear introduction to wavelet analysis and its application to geophysical signals. Tarasov et al [1998] give an example of its application to oscillations upstream of the Martian bow shock.…”
Section: Discussionmentioning
confidence: 99%
“…At Mars, detailed observations of plasma waves started with Phobos 2 [ Riedler et al , 1989; Grard et al , 1989; Sagdeev et al , 1990]. ULF waves near the proton gyrofrequency have been observed upstream of the Martian bow shock using both Phobos 2 data [ Russell et al , 1990, 1992; Tarasov et al , 1998; Delva and Dubinin , 1998] and MGS data [ Brain et al , 2002]. Initial reports of ULF waves within the magnetosheath and the magnetic pileup region as observed by MGS have also been made [ Cloutier et al , 1999; Crider , 1999; Bertucci et al , 2003b; Grebowsky et al , 2003].…”
Section: Introductionmentioning
confidence: 99%
“…For the same orbit, the magnetic field magnitude is plotted in Fig. 2(a) together with the low-frequency magnetic spectrum as result of a wavelet analysis (Tarasov et al, 1998). Just at the time (UT ≈ 04:55) where the "Phobos event" is seen as a strong magnetic field perturbation, a significant wave emission occurs near the proton cyclotron frequency Ω p (traced by a red line).…”
Section: The Phobos Eventsmentioning
confidence: 99%